Bulgecin A: The Key to a Broad‐Spectrum Inhibitor That Targets Lytic Transglycosylases - Allison H. Williams; Richard Wheeler; Constance Thiriau; Ahmed Haouz; Muhamed‐Kheir Taha; Ivo G. Boneca (MDPI AG, 2017)
Lytic transglycosylases (Lts) are involved in recycling, cell division, and metabolism of the peptidoglycan. They have been understudied for their usefulness as potential antibacterial targets due to their high redundancy in Gram‐negative bacteria. Bulgecin A is an O‐sulphonated glycopeptide that targets primarily soluble lytic tranglycosylases (Slt). It has been shown that bulgecin A increases the efficacy of β‐lactams that target penicillin bindings proteins (PBPs). Here, we present the high‐resolution crystal structure of LtgA from Neisseria meningitidis strain MC58, a membrane bound homolog of Escherichia coli Slt, in complex with bulgecin A. The LtgA‐bulgecin A complex reveals the mechanism of inhibition by bulgecin A at near atomic resolution. We further demonstrate that bulgecin A is not only a potent inhibitor of LtgA, but most importantly, it restores the efficacy of β‐lactam antibiotics in strains of N. meningitidis and Neisseria gonorrhoeae that have reduced susceptibility to β‐lactams. This is particularly relevant for N. gonorrhoeae where no vaccines are available. This work illustrates how best to target dangerous pathogens using a multiple drug target approach, a new and alternative approach to fighting antibiotic resistance.